Impact of Training Interventions on Physical Fitness in Children and Adolescent Handball Players: A Systematic Review and Meta-Analysis - Guillermo Barahona-Fuentes; Claudio Hinojosa-Torres; Sebastián Espoz-Lazo; Juan Pablo Zavala-Crichton; Guillermo Cortés-Roco; Rodrigo Yáñez-Sepúlveda; Fernando Alacid (Applied Sciences)
Introduction: The developmental stage of handball training is critical for the enhancement of physical fitness. However, there is considerable methodological variability in the interventions implemented to improve performance in children and adolescents. Objective: This paper examines the characteristics and effectiveness of physical training interventions on fitness components in youth handball players through a systematic review and meta-analysis. The review identifies and classifies the types of strategies and training modalities used, while the meta-analysis quantifies their effects on physical performance. Methods: A systematic search was conducted in the databases Web of Science, Scopus, SPORTDiscus, PubMed, and MEDLINE, identifying 61 studies. Of these, fifty-three were included in the systematic review and eight met the criteria for the meta-analysis. The analysis focused on interventions targeting 787 participants aged 8 to 18 years (15.4 mean) and addressing various components of physical fitness. The methodological quality and risk of bias were assessed using the Cochrane Risk of Bias Tool. Results: The meta-analysis revealed significant and positive effects of the interventions on physical performance. Plyometric training was associated with improvements in peak power (SMD = 1.41; 95% CI: 0.91 to 1.91), sprint performance (SMD = −1.27; 95% CI: −1.93 to −0.62), and jump ability (SMD = 3.69; 95% CI: 3.21 to 4.17). Resistance band training also showed a positive impact on jump height (SMD = 1.56; 95% CI: 1.25 to 1.86) and agility (SMD = 0.42; 95% CI: 0.19 to 0.65). Heterogeneity ranged from low to moderate across outcomes. Conclusion: Plyometric and resistance band training interventions are effective strategies to enhance physical fitness in young handball players. These findings provide a scientific basis for designing evidence-based training programs aimed at comprehensive physical development during formative athletic stages.